Code Switching of Preservice EFL Teachers in the Classroom at SMKN 1 Mataram - Nadine Vitalasma Manurung; Sudirman Wilian; Amrullah; Mahyuni (Journal of English Education Forum (JEEF), 2026)
This research aims to analyze the types of code switching, the factors, and the stages of English lesson in which code switching occurs in EFL classroom. This research employs a descriptive qualitative method. The data were collected through classroom teaching videos of two preservice teachers and small interviews. The data were analyzed through transcription, identification, classification, and interpretation based on Poplack’s (1980) and Hoffman’s (1991) theories. The findings reveal that three types of code switching were used, with intra-sentential switching as the most dominant type, followed by inter-sentential switching, and tag switching was the least frequent type. Furthermore, repetition for clarification was identified as the main factor influencing code switching, followed by talking about particular topics and the desire to be well understood. Code switching was found in almost all stages of the English lesson.